Obesity and the Risk of Developing Kidney Stones: A Systematic Review and Meta-analysis (Iranian Journal of Kidney Diseases, 2023)
Obesity is a growing problem that causes various metabolic disorders and organ dysfunction. The present systematic review and meta-analysis examined the impact of obesity on the risk of kidney stones. This meta-analysis was designed according to PRISMA guidelines. This extensive search was conducted on June 6, 2022, using relevant keywords in databases including PubMed, Web of Science, EMBASE, and Scopus. The data collected from observational studies were recorded in a datasheet. Odds Ratio (OR) and their 95% confidence intervals (CI) evaluated the overall effect size. The Cochran Q test and the statistic I2 were used to evaluate the heterogeneity of studies. Egger’s and Begg’s tests assessed potential publication bias. We included 15 observational studies published between 2005 to 2022 in this analysis. Compared to nonobese individuals, the OR for developing kidney stones in obese participants was 1.35 (95% CI: 1.20 to 1.52, P < .001). Considering geographical location, the OR for the risk of developing kidney stones in obese individuals was 1.51 (95% CI: 1.11 to 2.05, P = .009) in North America, 1.33 (95% CI: 1.16 to 1.51, P < .001) in Europe, and 1.18 (95% CI: 1.08 to 1.29, P < .001) in Asia. Begg’s test results (P = .625) demonstrated no publication bias. However, Egger’s test results (P = .005) indicated publication bias. Based on the results, obesity increases the risk of kidney stone development. Therefore, community health programs should be implemented to reduce the incidence of obesity and lower the risk of kidney stones.  DOI: 10.52547/ijkd.7223